(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article highlights various aspects of linguistics, focusing on different types of sentences and the challenges encountered in writing. It explores the intricacies of clauses, including simple, compound, complex, and compound-complex structures of English language. Furthermore, it examines the complexities of academic writing, particularly the compound-complex sentence, which researchers have identified as the least favored choice among students. Through an analysis of linguistic forms and writing challenges, it can shed lights on the complicated nature of language acquisition and composition.